Characterization of V-doped SnO2 nanoparticles at ambient and high pressures. (19th September 2018) - Ferrari, S; Bilovol, V; Pampillo, L G; Grinblat, F; Saccone, F D; Errandonea, D
Abstract: Nanoparticles of V-doped SnO2 with stoichiometry Sn1−x O2 Vx (x = 0.05, 0.075, 0.125) have been synthesized by a co-precipitation method. Their structural, vibrational, and nuclear properties have been characterized by x-ray Diffraction, Transmission Electron Microscopy, Energy Dispersive x-ray Spectroscopy, Raman Spectroscopy, and Mössbauer Spectroscopy (with 119 Sn probe) at ambient pressure. We also performed high-pressure synchrotron x-ray diffraction experiments. The structural behaviour was studied up to ∼10 GPa under quasi-hydrostatic conditions. It has been found that tin dioxide nanoparticles with V are more compressible than un-doped tin dioxide nanoparticles.